Potential Human Health Risk Assessment of Heavy Metals via the Consumption of Tilapia Oreochromis Mossambicus Collected from Contaminated and Uncontaminated Ponds - Yap, Chee Kong; Jusoh, Amiruddin; Leong, Wah June; Karami, Ali; Ong, Ghim Hock (Springer International Publishing, 2015)
Fish tilapia Oreochromis mossambicus were collected from a contaminated Seri Serdang (SS) pond potentially receiving domestic effluents and an uncontaminated pond from Universiti Putra Malaysia (UPM). The fish were dissected into four parts namely gills, muscles, intestines, and liver. All the fish parts were pooled and analyzed for the concentrations of Cd, Cu, Fe, Ni, Pb, and Zn. Generally, the concentrations of all metals were low in the edible muscle in comparison to the other parts of the fish. It was found that the levels of all the heavy metals in the different parts of fish collected from the SS were significantly (P < 0.05) higher than those from UPM, indicating greater metal bioavailabilities in the SS pond. The sediment data also showed a similar pattern with significantly (P < 0.05) higher metal concentrations in SS than in UPM, indicating higher metal contamination in SS. Potential health risk assessments based on provisional tolerable weekly intake (PTWI) and the amount of fish required to reach the PTWI values, estimated daily intake (EDI), and target hazard quotient (THQ) indicated that health risks associated with heavy metal exposure via consumption of the fish’s muscles were insignificant to human. Therefore, the consumption of the edible muscles of tilapia from both ponds should pose no toxicological risk of heavy metals since their levels are also below the recommended safety guidelines. While it is advisable to discard the livers, gills, and intestines of the two tilapia fish populations before consumption, there were no potential human health risks of heavy metals to the consumers on the fish muscle part.